Is neoadjuvant androgen deprivation therapy beneficial in prostate cancer treated with definitive radiotherapy? - Eom, Keun-Yong (Radiat Oncol J, 2014)
PURPOSE: To determine whether neoadjuvant androgen deprivation therapy (NADT) improves clinical outcomes in patients with prostate cancer treated with definitive radiotherapy. MATERIALS AND METHODS: We retrospectively reviewed medical records of 201 patients with prostate cancer treated with radiotherapy between January 1991 and December 2008. Of these, 156 patients with more than 3 years of follow-up were the subjects of this study. The median duration of follow-up was 91.2 months. NADT was given in 103 patients (66%) with median duration of 3.3 months (range, 1.0 to 7.7 months). Radiation dose was escalated gradually from 64 Gy to 81 Gy using intensity-modulated radiotherapy technique. RESULTS: Biochemical relapse-free survival (BCRFS) and overall survival (OS) of all patients were 72.6% and 90.7% at 5 years, respectively. BCRFS and OS of NADT group were 79.5% and 89.8% at 5 years and those of radiotherapy alone group were 58.8% and 92.3% at 5 years, respectively. Risk group (p = 0.010) and radiation dose ≥70 Gy (p = 0.017) affected BCRFS independently. NADT was a significant prognostic factor in univariate analysis, but not in multivariate analysis (p = 0.073). Radiation dose ≥70 Gy was only an independent factor for OS (p = 0.007; hazard ratio, 0.261; 95% confidence interval, 0.071-0.963). CONCLUSION: NADT prior to definitive radiotherapy did not result in significant benefit in terms of BCRFS and OS. NADT should not be performed routinely in the era of dose-escalated radiotherapy.